Social transformations in chinese societies : the official annual of the Hong Kong Sociological Association. - Bian, Yanjie, 1955-; Chan, Kwok B.; Cheung, Tak-sing (Social transformations in Chinese societies, 2005)
Social Transformations in Chinese Societies is the official annual of The Hong Kong Sociological Association. It publishes articles of original research that addresses theoretical, methodological, or substantive issues of sociological significance about or related to social transformations in Chinese societies. The focus is mainly on Hong Kong, Taiwan, the mainland, Singapore, and Chinese overseas. Review essays of exceptionally high quality are also welcome.